Organization for Environmental Management—National and Transnational - Jacoby, Neil H. (Management Science, 1973)
Environmental quality is the new social priority. Like previous major shifts in public values, it calls for changes in economic functions and resource allocations, and it requires new institutions for decision making and action. Criteria are proposed for choosing optimal governmental units to manage the principal environmental variables. Major gaps exist. At the Federal level, the Environmental Protection Agency should be supplemented by a new policy-oriented Institute for Environmental Studies and by programs of public education. State governments need executive agencies with integrated control over all variables. Metropolitan and regional authorities should be created to control land use planning and development. Environmental variables transcending national boundaries are now only partly managed by means of international treaties. A new World Oceanic and Atmospheric Regime is proposed to supply flexible and integrated control. The quality of environmental decisions would be raised greatly if decision-makers had available a socioeconomic model system of the United States.